Isolation and molecular identification of obligate thermophiles from hot springs in Ba Ria – Vung Tau and Khanh Hoa provinces, Vietnam - Kha Mong, Tran; Thanh Van, Le Thi; Vu Phong, Nguyen; Huu Tri, Nguyen (Vietnam Journal of Biotechnology, 2022)
Environments with temperatures from 50°C to 80°C are rare in nature and are almost exclusively associated with geothermal regions including hot springs, solar-heated soils and volcanic areas. Thermophilic bacteria already exist and prefer in such habitats. Since innate tolerance to thermal environment and potential chassis for extracellular enzymes such as lipase, protease and amylase, which are utilized widely in the industrial fermentation, thermophilic bacteria have been becoming one of the objects for microbiologists worldwide, recently. This study aimed to isolate and identify thermophilic bacteria from hot springs in several provinces in Vietnam such as Ba Ria - Vung Tau and Khanh Hoa. In the results, six moderate thermophilic bacterial strains (namely BM7, BS5, NS1, NS3, NS4, and NW6) that could grow at 55oC were purified from the hot spring ecosystems. All micro morphology of isolates were recorded as rod-shaped, Gram positive, and endospore forming. The results of 16S rDNA sequencing and phylogenetic analysis showed that these isolate belonged to group I of Bacillus genus (the thermophilic group). The isolated strains NS1, NS3, NS4, BS5, NW6 and BM7 were identified to belong to the Bacillus genus, species as Bacillus sp. Resulting strains are potential candidates for industrial applications due to its stable fitness in a hash environment, particularly at high temperature. In addition, this study provides a useful insight into the diverse community of thermophilic bacteria (Bacillus spp.) in several hot springs of Vietnam, that can be applied as bacterial cell factories to produce biomaterials, biofuels, or valuable compounds in the future.